A concise synthesis of thioaurones via NBS-induced cyclization of MOM-protected 2′-mercaptochalcones. Issue 6 (9th December 2022) - Nakamura, Akira; Rao, Fei; Ukiya, Kazuchika; Matsunaga, Riko; Ohira, Shin-ichiro; Maegawa, Tomohiro
Abstract : Herein we present a simple and efficient method for the synthesis of thioaurones (hemithioindigos) from MOM-protected 2′-mercaptochalcones with NBS and pyridine. Abstract : A mild and efficient approach for the synthesis of thioaurones via NBS-induced cyclization of methoxymethyl-protected mercapto-chalcones has been developed. This simple method is highly functional group tolerant and provides straightforward access to thioaurones in good to high yields.